Cervical ripening by using extra-amniotic dexamethasone infusion versus extra-amniotic saline infusion - Salman, Sawsan T.; Mohammed, Inaam F.; Saadi, Raakad K. (Journal of the Faculty of Medicine Baghdad, 2018)
Background: Induction of labour is a commonly practiced obstetric intervention designed to artificially initiate the process of cervical effacement to achieve vaginal delivery. Objective: examine the hypothesis that corticosteroids, when administered extra-amniotically, can enhance labor process and reduce the induction–delivery interval in comparison with folly’s and extra-amniotic saline infusion. Patients and methods: This, randomized case- control study was conducted on99 women, who were referred to the AL-Batool teaching Hospital in Diyala, Iraq, for induction of labor with a Bishop score of less than or equal to 5 from January 2014-March 2016, and divided into 2 groups, 1st group consist of 58 pregnant, a 26F catheter & and 20 mg of dexamethasone mixed with 20 ml of sterile saline solution infused extraamniotically. 2nd group consist of 41 pregnant, with the same size catheter attached to 500 ml of saline solution infused into the extra-amniotic space. Results: Administration of dexamethasone extraamnioticlly improve the Bishop score, reduce the time needed for expulsion of the catheter, shortening of 1st&2nd stage of labour without increasing the caesarean section rate. Conclusion: Extraamniotic administration of dexamethasone is effective & safe method for induction of labour. خلفية الموضوع:إن تحفيز الولادة من الممارسات الشائعة في مجال التوليد التي تستخدم لنضج عنق الرحم وإحداث الولادة اصطناعيا.لغرض تجنب الولادة بواسطة العملية الجراحية(القيصرية ) الهدف: لبيان مدى صحة النظرية التي تنص على إن استخدام مادة الكورتزون المحقونة خارج السائل الامينوسي تستطيع تحفيز عملية الولادة وتقلل المدة بين التحفيز و حصول الولادة بالمقارنة مع استخدام مادة المحلول الملحي النظامي المحقون بنفس الطريقة. طريقة الدراسة:دراسة تداخليه مقارنة سريريه أجريت على 99 امرأة حامل (حمل منفرد)وكانت مدة الحمل ما بين 37-42 أسبوع أحيلت إلى مستشفى البتول التعليمي –ديالى –العراق.لغرض تحفيز الولادة وكان مقياس بيشوب اقل من 5.وقد أجريت الدراسة للفترة من كانون الثاني 2014-آذار 2016.وقد تم تقسيم النساء الحوامل إلى مجموعتين: الأولى:تتكون من 58 امرأة حامل تم إدخال قسطرة فولي عن طريق عنق الرحم وتم حقن 20 ملغ من مادة الدكساميثازون مخلوطة مع 20 مل من المحلول الملحي النظامي. الثانية:تتكون من41 امرأة حامل تم إدخال قسطرة فولي بنفس الطريقة للمجموعة الأولى مع استبدال مادة الدكساميثازون ب 500 مل محلول ملحي نظامي بمعدل 5 قطرات بالدقيقة وفي كلتا المجموعتين ننتظر خروج الفولي من عنق الرحم تلقائيا وإذا لم يتم ذلك تلقائيا يتم استخراجه من عنق الرحم .وبعد ذلك يتم إعطاء المادة المحفزة للولادة(هرمون الولادة)لحين الحصول على ثلاث تقلصات خلال عشر دقائق. وبعد ساعتين يتم إجراء الفحص الداخلي للمريضة لغرض معرفة مدى تقدم مقياس بيشوب. وفي حال دخول المريضة إلى طور الولادة الفعال يتم استكمال خطة الدراسة.أما في حالة عدم حصول أي تقدم أو حصول تقدم بطئ يتم إيقاف المادة المحفزة للولادة وبذلك يكون تحفيز الولادة قد فشل. النتائج:حقن مادة الدكساميثازون خارج السائل الامينوسي عن طريق قسطرة فولي يحسن مقياس بيشوب ويقلل الفترة بين تحفيز الولادة وحصول الولادة مع تقليل مدة كل من المرحلة الأولى والثانية للولادة بدون أي زيادة في نسبة الولادة بواسطة العملية القيصرية. الاستنتاج:حقن مادة الدكساميثازون خارج السائل الامينوسي طريقة فعالة وآمنة ورخيصة يمكن استخدامها لتحفيز الولادة.